EVALUASI KEBIJAKAN TAMBAHAN PENGHASILAN APARATUR SIPIL NEGARA - Dede Riansyah (Mimbar Administrasi Mandiri, 2023)
This research aims to evaluate the policy of Additional Income for State Civil Apparatus (ASN). The method used by the author to conduct the research is a descriptive method with a qualitative approach. The theory used by the author to evaluate the policy of Additional Income for State Civil Apparatus is the theory of Dunn (2003) with indicators such as Effectiveness, Efficiency, Adequacy, Fairness, Responsiveness, Accuracy. Additional Income has a good impact on improving the performance of its employees, although not entirely, and for Additional Income, it is given regularly every month.